Electrical conductivity: foods - Vicente, A. A. (2011)
Electrical conductivity is a physical property of foods directly related to their ability to be heated by internal heat generation when subjected to an electric field. This entry analyzes the variables that can influence the value of electrical conductivity in foods and provides a review of the actual knowledge on this subject.